Projection-Based Inference in Randomised Clinical Trials - Zhang, Biao (International statistical review, 2019)
Covariate information is often available in randomised clinical trials for each subject prior to treatment assignment and is commonly utilised to make covariate adjustment for baseline characteristics predictive of the outcome in order to increase precision and improve power in the detection of a treatment effect. Motivated by a nonparametric covariance analysis, we study a projection approach to making objective covariate adjustment in randomised clinical trials on the basis of two unbiased estimating functions that decouple the outcome and covariate data. The proposed projection approach extends a weighted least-squares procedure by projecting one of the estimating functions onto the linear subspace spanned by the other estimating function that is E-ancillary for the average treatment effect. Compared with the weighted least-squares method, the projection method allows for objective inference on the average treatment effect by exploiting the treatment specific covariate–outcome associations. The resulting projection-based estimator of the average treatment effect is asymptotically efficient when the treatment-specific working regression models are correctly specified and is asymptotically more efficient than other existing competitors when the treatment-specific working regression models are misspecified. The proposed projection method is illustrated by an analysis of data from an HIV clinical trial. In a simulation study, we show that the proposed projection method compares favourably with its competitors in finite samples.